A COMPREHENSIVE OVERVIEW ON MANAGEMENT OF FUNGAL DISEASE BY VACCINES, DRAWBACKS, AND CHALLENGES - Sajid, Memona; Sana, Saba; Basharat, Fatima; Ahmad, Ali; Shaheen, Asif; Ilyas, Aqsa; Arif, Muhammad Athar; Atif, Khadija (Science Journal of University of Zakho, 2026)
Infections caused by fungi are a large and varied category of diseases that impact all living things on Earth. Underscoring their worldwide epidemiological effect, this review focusses on the categorization, pathogenic processes, and clinical symptoms of superficial and systemic mycoses. Morphological traits, virulence factors, and environmental adaptations that allow survival and infection are examined in relation to several fungal taxa. New opportunistic fungi and the rise of resistant strains are other topics of discussion. Antifungals and fungal vaccine and diagnostic methods are in the review. In order to better diagnose, prevent, and manage mycotic infections, it is essential to understand the biology and pathogenicity of fungi. This document also summarizes current research in medical mycology and suggests areas for future study to control fungal illnesses and to reduce their economic and health impacts.